2011
DOI: 10.1152/ajpcell.00001.2011
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone (PTH) rapidly enhances CFTR-mediated HCO3 secretion in intestinal epithelium-like Caco-2 monolayer: a novel ion regulatory action of PTH

Abstract: Laohapitakworn S, Thongbunchoo J, Nakkrasae L, Krishnamra N, Charoenphandhu N. Parathyroid hormone (PTH) rapidly enhances CFTR-mediated HCO 3 Ϫ secretion in intestinal epithelium-like Caco-2 monolayer: a novel ion regulatory action of PTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 64 publications
(89 reference statements)
8
38
1
Order By: Relevance
“…The presence of PTH, PTHrP, and their receptors in the same intestinal regions/cell lines, therefore, implicated the possibility of autocrine and paracrine actions of PTH and/or PTHrP (Li et al, 1995;Nemere & Larsson, 2002). Besides calciotropic action, PTH also plays an important role in regulating intestinal transport of other ions, such as phosphate and bicarbonate (Laohapitakworn, Thongbunchoo, Nakkrasae, Krishnamra, & Charoenphandhu, 2011;Nemere, 1996). By using perfused duodenal loop, PTH was found to stimulate phosphate absorption in the chick duodenum (Nemere, 1996), while an in vitro experiment in Caco-2 monolayer revealed that PTH rapidly and directly stimulated apical bicarbonate secretion through cystic fibrosis transmembrane conductance regulator in protein kinase A-and PI3K-dependent manner Laohapitakworn et al, 2011).…”
Section: Regulation Of Calcium Transport By the Parathyroid-kidney-inmentioning
confidence: 99%
“…The presence of PTH, PTHrP, and their receptors in the same intestinal regions/cell lines, therefore, implicated the possibility of autocrine and paracrine actions of PTH and/or PTHrP (Li et al, 1995;Nemere & Larsson, 2002). Besides calciotropic action, PTH also plays an important role in regulating intestinal transport of other ions, such as phosphate and bicarbonate (Laohapitakworn, Thongbunchoo, Nakkrasae, Krishnamra, & Charoenphandhu, 2011;Nemere, 1996). By using perfused duodenal loop, PTH was found to stimulate phosphate absorption in the chick duodenum (Nemere, 1996), while an in vitro experiment in Caco-2 monolayer revealed that PTH rapidly and directly stimulated apical bicarbonate secretion through cystic fibrosis transmembrane conductance regulator in protein kinase A-and PI3K-dependent manner Laohapitakworn et al, 2011).…”
Section: Regulation Of Calcium Transport By the Parathyroid-kidney-inmentioning
confidence: 99%
“…68 In addition, CFTR channel activity is known to be regulated by extracellular ion concentrations, including Cl À49 and HCO À 3 . 69 Recently, parathyroid hormone (PTH) has been shown to rapidly enhance CFTR-mediated HCO À 3 secretion, 70 while the thyroid hormones tri-iodothyronine and thyroxine have been reported to exert acute inhibition of CFTR channel gating. 71 Interestingly, CFTR has also been shown to be robustly activated by membrane stretch, indicating its mechnosensitive gating properties.…”
Section: Signalling Capacity Of Cftrmentioning
confidence: 99%
“…Both were applied at a concentration (C i ϭ 20 M) previously proven to completely inhibit PKA activity in live cells (51)(52)(53). Cells were incubated with the inhibitors for 30 -40 min before stimulation with CPT-cAMP or forskolin.…”
Section: Pka Activity Is the Major Contribution And Cftr-atpase Activmentioning
confidence: 99%